The effects of using mint on weight and biochemical blood tests in albino rabbit (Oryctolagus cuniculus) - Al-Kulabi, R. S.; Obead, W. F. (Scientific Progress & Innovations, 2025)
Medicinal plants are used in place of manufactured medications. We can learn about medicinal plants' biological activities from traditional medicine. Nowadays, the majority of nutraceuticals have gained popularity. Because herbal remedies had few or no negative effects, people began to trust them more than synthetic ones. In addition to being a useful medicinal plant for curing illnesses, mint may be utilized to make raw ingredients for the pharmaceutical sector. One of the main causes of metabolic syndrome, a global public health concern, is obesity. The current study's investigation focused on the anti-obesity properties of a Mentha spicata leaf extract, an herb used for centuries as a dietary supplement and traditional phytomedicine. Ten rabbits weighing between 2900 and 3350 g we divided the ten albino rabbits into two groups. for this experiment. The treatment group consisted of five, while the control group had five. For sixty days, the treatment group (TG) is fed only mint (40 mg/kg), while the control group (CG) is fed regular food. 24 hours following the end of therapy. Blood samples were taken, centrifuged (at 3000 g for 30 minutes), and serum was extracted for spectrophotometer measurements of HDL, LDL, triglycerides, and cholesterol using a commercial kit package. We conducted our analysis using standard commercial kits. According to the results, the weights of the white adipose tissue and body were considerably lower in the Mentha-supplemented group than in the CG group. Measurements of HDL, LDL, triglycerides, and cholesterol were made using blood samples in (CG) are 57.03±1.2; 74.63±1.5; 260.13±1.56; 211.71±1.04 respectively while in (TG) 56.53±1.42; 49.03±1.5; 188.02±0.76; 129.14±1.02. These findings imply that Mentha might aid in lowering diet-induced obesity and its associated issues and reducing overall cholesterol, LDL, and triglyceride levels in the treatment group's serum. This is a crucial scientific study to assess the plant's characteristics and determine how it can help prevent weight gain and eliminate fats that lead to numerous dangerous illnesses that cannot be ignored.